2020
DOI: 10.1186/s40658-020-0285-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two elastic motion correction approaches for whole-body PET/CT: motion deblurring vs gate-to-gate motion correction

Abstract: Background Respiratory motion in PET/CT leads to well-known image degrading effects commonly compensated using elastic motion correction approaches. Gate-to-gate motion correction techniques are promising tools for improving clinical PET data but suffer from relatively long reconstruction times. In this study, the performance of a fast elastic motion compensation approach based on motion deblurring (DEB-MC) was evaluated on patient and phantom data and compared to an EM-based fully 3D gate-to-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
4
6
0
Order By: Relevance
“…O u r r e s u l t s s h o w e d t h a t M C I R i m p r o v e d t h e quantification accuracy of lesions' SUVs and volumes caused by respiratory motion artifacts, which agrees with previous findings in other studies that used elastic respiratory motion correction algorithms (13,14,23,26). Pösse et al (23) reported that compared with uncorrected images, a gate-to-gate elastic motion compensation (G2G-MC) and an elastic motion deblurring (EMDB) algorithm yielded a 12% and 11% increase in lesion SUVs and an 18% and 28% decrease in lesion volume in 28 patients, respectively. In this study, we found that the SUVs increased by 11-15% while lesion volume decreased by 15-20% in a larger population using MCIR.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…O u r r e s u l t s s h o w e d t h a t M C I R i m p r o v e d t h e quantification accuracy of lesions' SUVs and volumes caused by respiratory motion artifacts, which agrees with previous findings in other studies that used elastic respiratory motion correction algorithms (13,14,23,26). Pösse et al (23) reported that compared with uncorrected images, a gate-to-gate elastic motion compensation (G2G-MC) and an elastic motion deblurring (EMDB) algorithm yielded a 12% and 11% increase in lesion SUVs and an 18% and 28% decrease in lesion volume in 28 patients, respectively. In this study, we found that the SUVs increased by 11-15% while lesion volume decreased by 15-20% in a larger population using MCIR.…”
Section: Discussionsupporting
confidence: 88%
“…Previous clinical studies found a large variance in respiratory amplitude at the diaphragm that can be from 0.4 to 3.8 cm in a superior-inferior direction depending on breathing patterns (2,22). The average motion extent of a lung tumor is usually in the order of 1 cm (23)(24)(25). Our phantom study also showed that the SUV and volume change caused by motion correction were associated with motion amplitudes (Figure 2).…”
Section: Discussionsupporting
confidence: 63%
“…Elastic motion correction (eMOCO) is usually used in PET/CT to correct for cardiac and respiratory motions in PET images, which has proven to be effective [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Signals from both sources were used for elastic motioncorrected PET reconstructions by first reconstructing the "optimal gate" comprising coincidence data from the narrowest signal amplitude interval covering 35% of the total data, giving a good compromise between motion resolution and data statistics, and then using mass-preserving optical flow techniques to determine a motion vector field between the gated and a static reconstruction. This vector field was then finally used in an effective deblurring step within a motion-corrected image reconstruction [18,19], resulting in BG-MC and DDG-MC datasets.…”
Section: Reconstructions and Motion Correctionmentioning
confidence: 99%
“…An important subset of the latter methods, software or data-driven gating (DDG) is based on analyzing measured PET raw data to calculate breathing signals instead of using additional hardware to record these signals, thus potentially simplifying clinical scans and increasing patient comfort [14][15][16][17]. Finally, fully motion-corrected reconstructions have been recently introduced by taking all measured PET data into account, rather than just a subset determined by a specified gating approach [18,19].…”
Section: Introductionmentioning
confidence: 99%